A Comparative Study of Three Min Respiratory Exercise Test & Six Min Walk Test as a Means to Score Breathlessness in COPD Patients and Normal Healthy Individuals - Shweta A. Panchbudhe1 , Umanjali Damke2 , Anjalee Chiwhane3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2011 update recommends thatthe management and treatment of COPD be made to combine the impact of disease and future risk ofexacerbation.Objectives: The aim of the study was to compare 3MRET & 6MWT as a means to score breathlessnessin COPD patients & normal healthy individuals along with to analyse and compare POD index of 3MRET& walking POD index of 6MWT in COPD patients, normal healthy individuals and to analyse whetherPOD index of 3MRET or walking POD index of 6MWT is a better means to score breathlessness in COPDpatients when compared with normal healthy individuals.Material and Method: It was observational comparative study conducted in respiratory Physiotherapy setup on 45 Normal healthy individuals and 45 COPD patients between the age group 30-50 years.Results: Study found that there is a statistically highly significant difference between POD index of 3MRETand walking pod index of 6MWT in COPD patients. There is a statistically highly significant differencebetween the POD index of 3 MRET and walking pod index of 6MWT in normal healthy individuals. MRETis a better means to score breathlessness in COPD patients as compared to normal healthy individuals. It wasfound that 3MRET is a better means to score breathlessness as compared to 6 min walk test